An Experimental Study for Reproduction of Biological Anomalies Reported in the Hoeven 1999 Crop Circle - Haselhoff, Eltjo; Boerman, Robert J.; Bobbink, Jan-Willem (Journal of Scientific Exploration, 2014)
This paper revisits the controversial case of a “crop circle,” a circular imprint of flattened crop, which appeared in the summer of 1999 in The Netherlands in the presence of an alleged eyewitness. Sampling of plant stems at various locations in the circle revealed a strong lengthening of the growth nodes, with a symmetrical distribution that was aligned with the flattened area itself. This effect has been attributed by some researchers to the effect of electromagnetic energy. In the case of this particular crop circle, the symmetry was indeed identical to the energy distribution of a spherical radiation source, which supported the claim of the eyewitness that a “ball of light” was hovering above the field at the time the crop circle was formed. However, others have suggested the results were simply the effect of sunlight, shadows, or wind over the flattened area, or some simple natural effect related to the fact that the crop in the circle had been flattened. The authors created a man-made control circle and repeated the growth node measurements that were carried out in the original 1999 crop circle using an identical test protocol. It was concluded that the findings in the 1999 circle could not be reproduced and hence remain anomalous. Keywords: crop circles—gravitropism—BOL model—pulvini—auxins